Application of spoligotyping in the understanding of the dynamics of Mycobacterium tuberculosis strains in high incidence communities - Streicher, Elizabeth Maria (University of Stellenbosch. Faculty of Health Sciences. Dept. of Biomedical Sciences., 2008)
Thesis (PhD (Biomedical Sciences. Molecular Biology and Human Genetics))--University of Stellenbosch, 2007.